In vitro and in vivo experiments with iron oxide nanoparticles functionalized with DEXTRAN or polyethylene glycol for medical applications: Magnetic targeting. Issue 4 (23rd January 2014) - Mojica Pisciotti, M. L.; Lima, E.; Vasquez Mansilla, M.; Tognoli, V. E.; Troiani, H. E.; Pasa, A. A.; Creczynski‐Pasa, T. B.; Silva, A. H.; Gurman, P.; Colombo, L.; Goya, G. F.; Lamagna, A.; et al.
ABSTRACT In this research work, DEXTRAN‐ and polyethylene glycol (PEG)‐coated iron‐oxide superparamagnetic nanoparticles were synthetized and their cytotoxicity and biodistribution assessed. Well‐crystalline hydrophobic Fe3O4 SPIONs were formed by a thermal decomposition process with d = 18 nm and σ = 2 nm; finally, the character of SPIONs was changed to hydrophilic by a post‐synthesis procedure with the functionalization of the SPIONs with PEG or DEXTRAN. The nanoparticles present high saturation magnetization and superparamagnetic behavior at room temperature, and the hydrodynamic diameters of DEXTRAN‐ and PEG‐coated SPIONs were measured as 170 and 120 nm, respectively. PEG‐ and DEXTRAN‐coated SPIONs have a Specific Power Absorption SPA of 320 and 400 W/g, respectively, in an ac magnetic field with amplitude of 13 kA/m and frequency of 256 kHz. In vitro studies using VERO and MDCK cell lineages were performed to study the cytotoxicity and cell uptake of the SPIONs. For both cell lineages, PEG‐ and DEXTRAN‐coated nanoparticles presented high cell viability for concentrations as high as 200 μg/mL. In vivo studies were conducted using BALB/c mice inoculating the SPIONs intravenously and exposing them to the presence of an external magnet located over the tumour. It was observed that the amount of PEG‐coated SPIONs in the tumor increased by up to 160% when using the external permanent magnetic as opposed to those animals that were not exposed to the external magnetic field. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 860–868, 2014.